PENGARUH MOTIVASI BELANJA HEDONIK DAN SUASANA TOKO TERHADAP PEMBELIAN IMPULSIF (Studi pada Konsumen Laris Toserba & Swalayan) - Catur Wulandari (Prospect : Jurnal Manajemen dan Akuntansi, 2024)
Modern retailers must have the right strategy so that consumers are interested in making purchases and especially consumers have impulsive purchases. There are several factors that can influence impulsive purchases, including hedonic and store atmosphere. Based on this, researchers are interested in conducting a study entitled "The Effect of Hedonic Shopping Motivation and Store Atmosphere on Impulsive Purchases (Study on Consumers of Laris Department Stores & Supermarkets in Purworejo)". The population in this study were consumers of Laris Department Stores & Supermarkets in Purworejo with an unknown number because there was no data. The sample was taken using a purposive sampling technique of 100 respondents. The results of the study show that the purchase variables of hedonic shopping motivation and store atmosphere have a positive and significant influence on impulsive purchases, both partially and simultaneously, thus both variables are important factors that influence impulsive purchasing decisions at Laris Toserba and Supermarket Purworejo.